Caracterização experimental do desempenho térmico na estação de aquecimento de um edifício gaioleiro - Mamede, M. (2011)
The energy conservation in buildings is one of the European Union main targets for 2020 to reduce energy dependence and greenhouse gases emissions. For residential buildings, the energy conservations measures are encouraged by several laws, and the thermal performance of building is regulated mainly by RCCTE. Old buildings use substantially different materials and construction solutions from those ones in new constructions, which require special studies to characterize their thermal performance and support the proper evaluation of retrofit measures. The “Pombalinos” and “Gaioleiros” buildings are widely studied from the structural and architectural point of view, with little information about their thermal characteristics. This communication presents the experimental results related to the evaluation of thermal performance characteristics in heating mode of a “Gaioleiro” building located in Lisbon.